2016
DOI: 10.1097/pcc.0000000000000641
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combined-Catheter to Monitor Left and Right Atrial Pressures

Abstract: This novel combined-catheter was safe and reliable at monitoring left and right atrial pressures, and infusion involved only one catheter without the disadvantages of the traditional method. This new novel method may be particularly useful in pediatric open-heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…If the LAP is too low, the anesthesiologist can provide uids. If the LAP is excessively high, regardless of whether the CVP is high or low, the anesthesiologist should use a positive inotropic medication instead of adding uid capacity 17 . Several studies have proven that the real-time hemodynamic input of the LAP can be used to re ect the left ventricular lling pressures variability in patients undergoing arterial switch surgery, common atrioventricular canal repair, and heart transplantation, among other procedures [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the LAP is too low, the anesthesiologist can provide uids. If the LAP is excessively high, regardless of whether the CVP is high or low, the anesthesiologist should use a positive inotropic medication instead of adding uid capacity 17 . Several studies have proven that the real-time hemodynamic input of the LAP can be used to re ect the left ventricular lling pressures variability in patients undergoing arterial switch surgery, common atrioventricular canal repair, and heart transplantation, among other procedures [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, given that cardiac disease could in uence LA/RA size and hence ideal length, the parameters of RA diameter were incorporated. Ding and co-workers indicated that the catheter length in the LA should not be too long, and its length is usually 1.5-2.0 cm; however, no current data regarding the length or appropriate location and its exact impact factors are available 17 . Our ndings clearly showed that age, height, and weight correlated signi cantly with the OD of insertion.…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon positions the tip of the single-lumen catheter from right to left in the atrium during the transatrial surgical procedure after repairing the primary defect. This method avoids bleeding complications; however, the risk of infection or obstruction of the superior vena cava is increased [Zahorec 1997;Rao 1993;Ding 2016]. Besides, it is difficult to puncture the jugular vein twice in pediatric patients, especially in newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Before removal of direct transthoracic monitoring catheters, it's recommended that cross-matched blood and platelets be available and that patients be checked for coagulopathies [Ding 2016].…”
Section: Discussionmentioning
confidence: 99%
“…After CPB, the triple-lumen catheter in the IJV and the single-lumen catheter in the LA are used to monitor CVP and LAP, respectively. Yan et al 5 from Fuwai Hospital invented a modified triple-lumen catheter that incorporates a single lumen microtube that can be placed in the left atrium intraoperatively, avoiding the traditional "double-stick" technique in IJV. The spiraled distal tip of the microtube reduces the chance of migration into right atrium (RA).…”
Section: Pulmonary Artery Cathetermentioning
confidence: 99%